Management Education in Kerala-Impact on Employability - K.M. Pradeep; S. Edmund Christopher and D. Kinslin
Kerala is the State having height in Human development Index in the Country. It has got the highest literacy rate and also number one in female literacy. In case of employment the state is not in the list of toppers in the country. We are trying to analyses why the employability is not as high as education in the state. We could find out many variables contributing to it. Primarily we are focusing how Management education in the state affects the corporate readiness of the students of Kerala, also we are trying to find out how can we improve upon and trying to suggest the required connect from the study.